DESAIN DAN IMPLEMENTASI SISTEM INFORMASI INVENTORY HARDWARE LABORATORIUM APLIKASI KOMPUTER BERBASIS WEB PADA STMIK PPKIA PRADNYA PARAMITA MALANG - Mariyam, Nisa Lutfiyah Siti; Utsalina, Dwi Safiroh (DINAMIKA DOTCOM, 2013)
Laboratory hardware inventory information system is a web -based computer applications are designed with the aim to improve the performance of data processing hardware inventory through the use of information systems hardware inventory. So the data processing errors and difficulty controlling the data can be minimized after the hardware inventory information system web-based computer application laboratory at STMIK PPKIA Pradnya PARAMITA Malang.In this study using the methods of data collection and system development methods. In the interview method of data collection was conducted at the laboratory hardware inventory, as well as observations by direct observation in the lab inventory . In addition, the literature study was also conducted by collecting data either from the library or browsing of the Internet. Systems development method used is the method of SDLC ( System Development Life Cycle ) such as system analysis , system design , system implementation , and operation and maintenance system.From the research that has been done can be obtained results awakening hardware inventory information system that assists students to obtain information about the hardware inventory , hardware as well as facilitate staff in preparing reports on the application of laboratory hardware inventory STMIK Pradnya PPKIA PARAMITA Malang . Key words : Information Systems, Inventory, hardaware, Laboratory